Chapter 12: Emergency Care (Pharmacy Essentials: A Compact Guide for Students and Practitioners, 2025)
AuthorDr. Aditi Naidu Patti, Assistant Professor, Department of Pharmacy Practice, Vignan Institute of Pharmaceutical Technology, Duvvada, Visakhapatnam, Andhra Pradesh, IndiaAbstractEmergency care in pharmacy settings involves medication management, first response capabilities, toxicology knowledge, and organizational protocols for crisis situations. Emergency medications maintained in pharmacy inventories include life-saving agents addressing anaphylaxis (epinephrine), opioid overdose (naloxone), hypoglycemia (dextrose, glucagon), cardiac arrest (atropine, amiodarone), and status epilepticus (benzodiazepines, levetiracetam), with pharmacist responsibilities including proper storage, expiration monitoring, dosing reference maintenance, and team education regarding appropriate administration. First aid in pharmacy settings requires preparation for common medical emergencies including cardiac events, allergic reactions, hypoglycemia, seizures, bleeding, and respiratory distress, with pharmacist training in basic life support, automated external defibrillator operation, and emergency response protocols coordinated with local emergency medical services. Toxicology basics essential for pharmacist practice include recognition of common poisoning presentations, initial management approaches for substance overdoses, familiarity with antidote mechanisms and indications, poison control center collaboration protocols, and triage decision-making for determining appropriate level of care. Crisis management extends beyond medical emergencies to address disaster response, medication supply chain disruptions, security incidents, and public health emergencies, requiring established communication hierarchies, essential medication stockpiles, alternative dispensing procedures, and coordination with government agencies and healthcare systems. This emergency preparedness helps pharmacists during both individual medical crises and larger-scale emergencies affecting medication access and public healthKeywords: Emergency Response; Overdose Management; Antidote; Disaster Preparedness; Life-Threatening ConditionsVIEW PDF